Pengembangan Media Promosi Digital Umkm Gaya Ampera Melalui Perancangan Website Berbasis Site 123 - Enzialita Adrin Faiqah; Nafizhsa Aqshonia Anelka; Aisyah Putri; Zulfitri Yani; Sularno Sularno (CV. ITTC INDONESIA, 2026)
Small and medium enterprises (SMEs) in the culinary sector commonly face limitations in promotional reach due to reliance on conventional word-of-mouth marketing. Gaya Ampera, a traditional Minangkabau culinary SME established in Padang in 2021, had not previously utilized any digital promotional medium. This community service activity aimed to develop a promotional website using the SITE123 platform to strengthen Gaya Ampera's digital branding and market accessibility. The method comprised field observation, a structured interview with the business owner, needs analysis, website design and development, and implementation evaluation. The resulting website features pages for Home, About, Favorite Menu, reasons to choose Gaya Ampera, a complete menu catalogue, catering services, call to action, contact information, location map, and a contact form. The website contributes to a more professional business image, broader promotional reach beyond the physical location, and easier customer access to product and service information. This confirms that website-based digital media represents an effective and accessible promotional solution for culinary SMEs.